Paul Ricœur sobre memória coletiva: a coesão da vida social - Vendra, Maria Cristina Clorinda (Voluntas: Revista Internacional de Filosofia, 2019)
The aim of this article is to present a critical reconstruction of Ricœur’s analysis of the complex phenomenon of memory as a collective act of recollection. By focusing the attention on memory as a collective practice, through the use of resources drawn from phenomenology, sociology, and history, I seek to outline the role and the construction of the collective memorial discourse and its foundations, looking particularly at the eighth chapter of the third volume of Time and Narrative and at the work Memory, History, Forgetting. I will show that the identification and the location of ourselves with others in social collectivities imply to negotiate a gap between subjective and cosmic time. Temporality comes, then, in the plural: our being in time is not merely personal, but rather we are originally involved in a social and historical framework.